Experimental study on controlled-release inhibitor foam for restraining spontaneous combustion of coal. Issue 4 (July 2020) - Zhang, Xun; Yang, Jing; Xie, Pengfei; Liu, Hao; Deng, Qiang; Dai, Fengwei
A new method is proposed based on temperature-controlled self-reaction to generate and release inhibitors in the form of foam at a specific temperature, which can overcome the disadvantages of short effective time and low efficiency in the inhibition of the spontaneous combustion of coal when inhibitors are released in advance, and greatly increase the action range of inhibitor through foam diffusion. The proposed temperature-controlled foaming system was prepared with hollow spheres as solution carriers, NaHCO3 and acetic acid as basic reactants, reaction-generated CO2 as foaming gas, sodium dodecyl sulfate and sodium carboxymethyl cellulose as foaming additives, NaCl, MgCl2 and CaCl2 as additives to enhance inhibition effect, and temperature sensitive paraffin as insulating material to generate and release inhibitor foam. The effects of releasing foam on restraining the spontaneous combustion of coal were studied based on the experimental analysis of the optimum ratio of reactants and additives, hollow sphere parameters, released temperature of the foam and variation rule of CO generated by coal oxidation. The obtained results showed that the released temperature of foam was 59–61°C and the covered area of pulverized coal by inhibitor foam was 12.9–13.9 times higher than when it was directly wetted by inhibitor solution. The total effects of inhibition and inerting were achieved after pulverized coal was wetted with inhibitor foam and the efficiency of restraining the spontaneous combustion of coal reached 88.51–97.06% when temperature was increased to 160°C.